A STUDY OF EFFECT OF DEMOGRAPHIC CHARACTERISTICS ON FINANCIAL RISK TOLERANCE OF INDIVIDUAL INVESTORS - Sarfaraz Ansari; Dr. Yogeshwari Phatak (International Journal of Management Studies (IJMS), 2021)
Financial risk tolerance (FRT) level can be defined as minimum risk bearing capacity of investors while taking investment decision. It is one of the most important influencing factors that control the investors mind to select particular investment avenue. The present study analyzes the effect of demographic effect of investors on risk tolerance level of investors. The data was collected through questionnaire on 974 individual investors. Age, Income, Gender, Occupation and Education was taken as independent variables while financial risk tolerance was taken as dependent variable. Financial risk tolerance was measured through scale developed by Grable and Lytton (1999). The study found that majority of investors belong to average risk tolerance category and all demographic variables i.e., age, gender, income, occupation and education significantly affects financial risk tolerance of investors.